Representing foreign workers in the private security industry: a South African perspective on trade union engagement. Issue 1 (4th February 2014) - Gordon, Steven; Maharaj, Brij
ABSTRACT: In recent years South African cities have become home to a large number of undocumented migrant workers. If trade unions do not organise undocumented migrant workers, it opens up such workers to exploitation and maltreatment by employers, thereby creating a split labour market that undermines the entire labour movement. This article focuses on the responses of the national trade union movement in the private security sector to the presence of undocumented workers at the grassroots level. Using a case study approach, we find that the pressures of labour market informalisation in the industry prompt unions to seek to maintain and advance their position from their traditional support base of citizen workers rather than attempt to include new groups. The failure to engage is reinforced by anti-immigrant attitudes which link foreigners with problems in the industry such as low wages and portrays such workers as co-conspirators rather than comrades. While justice and solidarity have always been the foundation of trade unionism in South Africa, the movement is in danger of failing this test if the current situation in terms of the exclusion of undocumented foreign workers persists.